2011
DOI: 10.1007/s10059-011-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hempseed Meal Intake and Linoleic Acid on Drosophila Models of Neurodegenerative Diseases and Hypercholesterolemia

Abstract: Hempseed is rich in polyunsaturated fatty acids (PUFAs), which have potential as therapeutic compounds for the treatment of neurodegenerative and cardiovascular disease. However, the effect of hempseed meal (HSM) intake on the animal models of these diseases has yet to be elucidated. In this study, we assessed the effects of the intake of HSM and PUFAs on oxidative stress, cytotoxicity and neurological phenotypes, and cholesterol uptake, using Drosophila models. HSM intake was shown to reduce H 2 O 2 toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…The ability of the dietary hempseeds supplementation to reduce the dietary cholesterol uptake in the presence of an enriched-cholesterol diet, was observed also by Lee and co-workers [ 134 ] in Drosophila melanogaster and was attributed to the ability of some hempseed components, PUFAs LA and ALA in primis , to down-regulate the expression of the Niemann-Pick C1-Like 1 (NPC1L1) gene, coding for a key intestinal cholesterol absorption protein. By contrast, Prociuk and colleagues [ 135 ] found that 8 weeks of 10% hempseeds supplementation of a cholesterol-enriched diet in albino New Zealand rabbits did not decrease the cholesterol plasma level but led to an approximately 12-fold increase in the plasma GLA level, resulting in a normalization of the platelet aggregation.…”
Section: Hempseed Dietary Supplementationmentioning
confidence: 69%
“…The ability of the dietary hempseeds supplementation to reduce the dietary cholesterol uptake in the presence of an enriched-cholesterol diet, was observed also by Lee and co-workers [ 134 ] in Drosophila melanogaster and was attributed to the ability of some hempseed components, PUFAs LA and ALA in primis , to down-regulate the expression of the Niemann-Pick C1-Like 1 (NPC1L1) gene, coding for a key intestinal cholesterol absorption protein. By contrast, Prociuk and colleagues [ 135 ] found that 8 weeks of 10% hempseeds supplementation of a cholesterol-enriched diet in albino New Zealand rabbits did not decrease the cholesterol plasma level but led to an approximately 12-fold increase in the plasma GLA level, resulting in a normalization of the platelet aggregation.…”
Section: Hempseed Dietary Supplementationmentioning
confidence: 69%
“…Linoleic acid, 9(10)-EpOME and DHA were involved in linoleic acid metabolism in AD. Some studied were suggested that linoleic acid as a polyunsaturated essential fatty acids with neuroprotective activity could hold back the uptake of cholesterol and the cytotoxicity of Aβ42 in drosophila model of AD 32,33 . The increased accumulation of Aβ induces the production of free radicals, which resulting in the increase of lipid peroxidation in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Hempseed flour reduced the impact of paraquat on climbing ability and the duration of tonic immobility in T. castaneum . Hempseed flour was shown to act as an antioxidant in a fruit fly PD model, although no beneficial effects on the locomotion phenotype were observed (Lee et al, ). Gou‐teng tea also reduced the impact of paraquat on climbing ability and the duration of tonic immobility.…”
Section: Discussionmentioning
confidence: 99%